2021
DOI: 10.3390/ijms22052276
|View full text |Cite
|
Sign up to set email alerts
|

Time-Resolved scRNA-Seq Tracks the Adaptation of a Sensitive MCL Cell Line to Ibrutinib Treatment

Abstract: Since the approval of ibrutinib for relapsed/refractory mantle cell lymphoma (MCL), the treatment of this rare mature B-cell neoplasm has taken a great leap forward. Despite promising efficacy of the Bruton tyrosine kinase inhibitor, resistance arises inevitably and the underlying mechanisms remain to be elucidated. Here, we aimed to decipher the response of a sensitive MCL cell line treated with ibrutinib using time-resolved single-cell RNA sequencing. The analysis uncovered five subpopulations and their indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 59 publications
(31 reference statements)
1
9
0
Order By: Relevance
“…We also believe that a deep characterization at single-cell resolution of human cell lines will allow for a better usage of these omnipresent models in molecular/cell biology and pharmacology. Many single-cell datasets measured on cell lines exist beyond the one described here (SY5Y cells) on other cell lines from neuroblastoma [14], breast cancer [48], and lymphoblasts [49,50]. Fueled by current technological advances provided by, e.g., CITE-seq, cell line single-cell datasets can be produced in even higher numbers and for more experimental contexts, towards the generation of an integrated and comprehensive Human Cell Line Atlas.…”
Section: Discussionmentioning
confidence: 99%
“…We also believe that a deep characterization at single-cell resolution of human cell lines will allow for a better usage of these omnipresent models in molecular/cell biology and pharmacology. Many single-cell datasets measured on cell lines exist beyond the one described here (SY5Y cells) on other cell lines from neuroblastoma [14], breast cancer [48], and lymphoblasts [49,50]. Fueled by current technological advances provided by, e.g., CITE-seq, cell line single-cell datasets can be produced in even higher numbers and for more experimental contexts, towards the generation of an integrated and comprehensive Human Cell Line Atlas.…”
Section: Discussionmentioning
confidence: 99%
“…In a prior scRNA-seq analysis, we tracked an ibrutinib-sensitive MCL cell line across 2 d treatment with ibrutinib, as adaptations in gene expression could be associated with higher resistance to the BTK inhibitor [ 7 ]. Although the four surviving subpopulations showed a common response, the existence of two metabolic distinct subgroups indicated that we had not caught the finally resistant cells.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we performed a bulk RNA-seq analysis to decipher the features of MCL cells that were finally adapted to ibrutinib by prolonging the treatment of REC-1 cells up to 4 days (d). As RNA-seq data corroborated increased activity of oxidative phosphorylation in resisting cells, we focused on OXPHOS and the previously postulated CD52 as potential targets [ 7 ].…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Targeted therapies are especially prone to resistance with relatively simple mutations in the target protein or pathway, but thanks to methodological advances, we are starting to understand much more complex signaling networks that can create forms of resistance beyond classic genetics. Single-cell technologies, immune-phenotyping, single-cell transcriptome profiling, functional studies, and chromatin mapping, all integrated with bioinformatic analytic tools, may help understand the supportive role of the immune microenvironment in CLL progression and the co-evolution of cells involved in the disease, directly or indirectly [5,41,52,[82][83][84].…”
Section: Role Of the Immune System In Resistance To Treatmentmentioning
confidence: 99%